The software IP detective's handbook : measurement, comparison, and infringement detection - Zeidman, Robert (Upper Saddle River, New Jersey : Prentice-Hall, 2011)
This book will help you understand the key concepts that underlie software IP analysis ; Compare and correlate source code; Identify and measure copying; Uncover signs of copying in object code when source code is inaccessible; Compare functional source code statements to nonfunctional comments; Confirm suspected theft or infringement; Track malware and third-party code in applications; Use software clean rooms to avoid IP infringement; Understand IP issues associated with open source; and DMCA.
Part 1. Introduction -- Part 2. Software -- Part 3. Intellectual property -- Part 4. Source code differentiation -- Part 5. Source code correlation -- Part 6. Object and sourcce/Object code correlation -- Part 8. Detecting software IP theft and infringement -- Part 9. Miscellaneous topics -- Part 10. Conclusion: past, present, and future.
Includes bibliographical references and index.
Keywords: INTELLECTUAL PROPERTY